Peran Guru dalam Pembelajaran Seni Budaya (Tari Kreasi) Siswa Kelas IX.1 di SMP YLPI P. Pekanbaru - Mutiara Nuzulul Fitri; Yahyar Erawati (Advances In Education Journal, 2025)
This study explores the teacher’s role in creative dance learning within arts and culture education in class IX.1 of SMP YLPI P. Marpoyan Pekanbaru during the 2025/2026 academic year. Using a descriptive qualitative approach, data were collected through non-participant observation, interviews, and documentation. The research involved one arts teacher and 17 students. Findings reveal that the teacher fulfills multiple roles including educator, motivator, guide, and facilitator by adapting to student needs, interests, and learning styles. These roles help create a supportive environment for students to explore and develop their creativity. The study also highlights the importance of innovative and personalized strategies to overcome low interest in dance, particularly among male students. The findings confirm that a teacher’s comprehensive role is essential in enhancing learning quality and supporting students' character and creative development.